Write more, publish more, stress less! : five key principles for a creative and sustainable scholarly practice - Stevens, Dannelle D. (Routledge, 2023)
This book offers you five keys that will bolster your knowledge of academic writing. Also it enables you to develop a manageable, sustainable and enjoyable writing practice. It is a comprehensive and practical guide that will help you publish and flourish.